2023
DOI: 10.3390/ijms241411773
|View full text |Cite
|
Sign up to set email alerts
|

Sugar Starvation Disrupts Lipid Breakdown by Inducing Autophagy in Embryonic Axes of Lupin (Lupinus spp.) Germinating Seeds

Abstract: Under nutrient deficiency or starvation conditions, the mobilization of storage compounds during seed germination is enhanced to primarily supply respiratory substrates and hence increase the potential of cell survival. Nevertheless, we found that, under sugar starvation conditions in isolated embryonic axes of white lupin (Lupinus albus L.) and Andean lupin (Lupinus mutabilis Sweet) cultured in vitro for 96 h, the disruption of lipid breakdown occurs, as was reflected in the higher lipid content in the sugar-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 69 publications
0
12
0
Order By: Relevance
“…The action of exogenous asparagine, which slowed down the degradation of autophagic bodies and decreased lipolytic activity in the −S+Asn axes, convinced us to use this amino acid in our research concerning the role of vacuolar lipases in autophagic body degradation. The comparison of our previously obtained results [ 15 , 16 , 18 ] with the currently performed transcriptome analysis (NGS and SRA databases, BioProject accession number for white lupin: PRJNA953600, and Andean lupin: PRJNA953433, deposited in 2023) suggested that vacuolar lipases have a high potential to be involved in the degradation of autophagic bodies in plants. This preliminary study provides new insights into one of the final, poorly understood stages of autophagy in plants, which is the degradation of autophagic bodies.…”
Section: Introductionmentioning
confidence: 76%
See 4 more Smart Citations
“…The action of exogenous asparagine, which slowed down the degradation of autophagic bodies and decreased lipolytic activity in the −S+Asn axes, convinced us to use this amino acid in our research concerning the role of vacuolar lipases in autophagic body degradation. The comparison of our previously obtained results [ 15 , 16 , 18 ] with the currently performed transcriptome analysis (NGS and SRA databases, BioProject accession number for white lupin: PRJNA953600, and Andean lupin: PRJNA953433, deposited in 2023) suggested that vacuolar lipases have a high potential to be involved in the degradation of autophagic bodies in plants. This preliminary study provides new insights into one of the final, poorly understood stages of autophagy in plants, which is the degradation of autophagic bodies.…”
Section: Introductionmentioning
confidence: 76%
“…Research was performed on the embryonic axes isolated from the imbibed seeds of the white lupin ( Lupinus albus L.) and Andean lupin ( Lupinus mutabilis Sweet) and cultured in vitro for 96 h on a liquid mineral Heller medium [ 22 ] with or without 60 mM of sucrose (+S and −S, respectively) and with 35 mM of asparagine (−S+Asn and +S+Asn, respectively). A detailed description of the morpho-physiological parameters of the 96 h lupin embryonic axes was published previously [ 16 , 18 ]. Based on the results of the mass sequencing of the transcriptomes of the white and Andean lupin isolated embryonic axes cultured in vitro for 96 h, we identified 90 and 111 transcripts of the genes encoding lipases for the embryonic axes of the white lupin and Andean lupin, respectively ( Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations